EPIDEMIOLOGICAL AND ETIOLOGICAL PROFILE OF THE CAUSES OF HOSPITALIZATION FOR MENINGITIS IN CASCAVEL/PR OF 2022/2023 - Enderle Bernardi, Laura (2024)
Meningitis is a notice appeal disease, of high epidemiological relevance for being highly infectious. It’s of utmost importance to verify and determine an epidemiological profile of the location to comprehend the most prevailing etiology for a given risk population. This article’s objective is to evaluate the epidemiological profile for the population of Cascavel-PR that were affected by meningitis between 2023 and 2024, obtaining the following informations: race, age group, etiology, notification month, confirmation standards and evolution. These informations were evaluated with the proposal of stablishing a local scenario for meningitis and health orientations. The methods used in this study were composed by Cascavel-PR’s population that had a confirmed diagnosis of meningitis. The data was collected from DATASUS. Results: of the 146 patients, the most affected breed was the Caucasian (71,4%), of these, 87 (59,6%) were men and 59 (40,4%) women. The most prevailing age group was between 40 and 59 years old (19,9%). The most prevailing etiology was the viral meningitis, which has stated 50 cases (34,2%), followed by other bacteria’s meningitis (31,6%). October was the month which stated the most notifications. Of the confirming methods, the most applied one was the chemocytological one, with 88 cases (60,5%), followed by the culture method, that stated 26 cases (17,8%). The main evolution of the meningitis’ cases was by hospital recharge (75,8%), with 8 deaths (5,5%). Conclusion: the present study analyzed that the epidemiological data is compatible with the national data. Further stated the importance of using the right methods for diagnosing meningitis, avoiding subnotificações, needless expenses and bringing a better treatment for the patients.